Student Character Education Model In Elementary Schools And Madrasah Ibtidaiyah In Banda Aceh City - Ismail, Zahrila; Walidin, Warul; Gade, Syahbuddin (Jurnal Ilmu Sosial Mamangan, 2024)
This study aims to examine the Model of Student Character Education in Elementary Schools and Madrasah Ibtidaiyah in Banda Aceh City. The type of research used is field research, a qualitative approach with a descriptive-analytical method. The research location is two Elementary Schools (SD) and two Madrasah Ibtidaiyah (MI) in Banda Aceh. Data collection techniques through interviews, observations and documentation studies. The theories used are Thomas Lickona's character education theory, Ratna Megawangi 's PHBK (Character-Based Holistic Education) character education theory and Imam Al-Ghazali's character education theory. The results of the study found that first, the planning of student character education in Elementary Schools and Madrasah Ibtidaiyah in Banda Aceh City was carried out through preparation of learning programs, preparation and development of learning methods, development of teaching materials, determining learning media and developing assessment systems, preparation of learning rosters and learning schedules. Second; the implementation of student character education in Elementary Schools and Madrasah Ibtidaiyah in Banda Aceh City is carried out through intracurricular, co-curricular and extracurricular components. Third; the implications and models of student character education in Elementary Schools and Madrasah Ibtidaiyah in Banda Aceh City gain a comprehensive understanding and experience of religious values, discipline values, independent values and responsibility values in school life, family and society. The novelty findings of this study are that the character education model in Elementary Schools and Madrasah Ibtidaiyah in Banda Aceh City is based on role models or uswah hasanah.